Fucoxanthin extraction and fatty acid analysis of Sargassum binderi and S. duplicatum - Noviendri, Dedi; Jaswir, Irwandi; Salleh, Hamzah Mohd.; Bakhtiar, M. Taher; Kazuo, Miyashita; Nazaruddin, Ramli (Academic Journals, 2011)
Fucoxanthin has been successfully extracted and purified from two species of Malaysian brown seaweeds, namely S. binderi and S. duplicatum. The purity of the fucoxanthin is >99% as indicated by HPLC analysis. Fucoxanthin content, total lipid and fatty acid composition of the seaweeds showed that both samples contained a considerable amount of fucoxanthin and total lipid. The amount of fucoxanthin and total lipid contents of S. duplicatum (1.01 ± 0.10 and 21.3 ± 0.10 mg/g dry-weight, respectively) was significantly higher than those of S. binderi (0.73 ± 0.39 and16.6 ± 4.10, respectively). Both types of seaweeds also contained a considerable amount of unsaturated fatty acids. However, in terms of docosahexanoic acid, eicosapentanoic acid, arachidonic acid, linoleic acid and alpha-linolenic acid contents, S. duplicatum was found to be higher (0.76, 2.55, 13.64, 5.81 and 5.35%, respectively) than S. binderi (0.70, 1.82, 9.13, 6.37 and 4.39%, respectively). For saturated fatty acids, palmitic (C16:0) was found to be the major fatty acid in both samples studied.